Teachers’ Challenges in Teaching English Writing Skills for Visually Impaired Students at Indonesian Special Senior High Schools - Prih Febtiningsih; Ardiya; Agung Prasetyo Wibowo (Universitas Lancang Kuning, 2021)
Teaching English at Indonesian special senior high schools is applied based on the curriculum determined by the government. However, there were some problems found in English language teaching for visually impaired students especially in writing. This research aimed to investigate the teachers’ challenges in teaching English writing for visually impaired students. The respondents were taken purposively, namely the English teachers at Indonesian special senior high schools for visually impaired students namely SLB Sri Mujinab, SLB Negeri Pembina and SLB Kasih Ibu. The data for the research were collected from semi-structured interview conducted to get specific information about what challenges encountered by the English teachers teaching writing skills for students with visual impairment. The challenges encountered by the teachers in teaching writing were inappropriateness of curriculum and syllabus with the students’ need, time constraint of teaching, lack of learning media, lack of teaching strategy, inappropriateness of teacher’s qualification, and students’ attitude problem. These challenges made the teachers difficult in teaching English writing. Keywords: Teaching Writing, Visual Impairment, Teachers’ Challenges, English Language Teaching